Innovation in Portuguese schools: what is the grammar of its conceptualization? - Martins, Natália; Palmeirão, Cristina; Matias Alves, José (Frontiers in Education, 2025)
Massification of schooling ensured all students access to education. Until now, the industrial school model was ideal, however, due to the coexistence of cultural and socioeconomic differences, it has become ineffective. Consequently, problems of school failure, dropout and hidden school dropout related to the school mission emerged. Thus, the solution reached, after several relatively unsuccessful “top-down” reforms, is the emergence of a “bottom-up” change which allows schools to reconstruct while adapting to changes in society and addressing the needs of each student. Given this, there is a need to alter the grammar of schooling which remains rooted in time and has become an obstacle to students' learning. In 2018, innovation began to be seen as a possible pathway toward constructing a more personalized education through the implementation of innovation plans in schools. Accordingly, we created and applied an analysis matrix to 66 of the 88 innovation plans pertaining to the 2022/2023 school year, with the aim of answering the following questions: what problems or difficulties have been diagnosed in the design and development of the innovation projects? What variables are used to solve the diagnosed problems? Do the areas and dimensions utilized entail effective innovation in organizational and pedagogical practices capable of improving educational processes and outcomes? Findings indicate that, considering the reference table, a greater investment by schools is needed for a desired profound change in the grammar of schooling. It is noted that, given the identified problems, mainly focusing on school failure, there is a clear emphasis by most plans on changes in teachers' professional development and evaluation strategies. Nevertheless, it seems clear that the macro-level dimensions were the most neglected, with a significant number of plans lacking information regarding the school organization and management, the school environment and top leadership. Therefore, these data suggest that at the micro-level, which refers to educational action in the classroom, all dimensions were very evidently considered by most plans, ignoring organizational dimensions that have the potential to change the working models of teachers and students.